(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Plant disease detection is essential for reducing plant and agricultural product productivity and quantity losses. Controlling plant diseases by hand is a difficult task. It necessitates a tremendous deal of effort, knowledge of plant diseases, and, in many cases, an unnecessary amount of processing time. Image acquisition, image pre-processing, segmentation, feature extraction, and classification are the five primary phases in the proposed plant leaf disease detection system. Images of damaged leaves are being collected and image pre-processing is being used to improve them